Metabolic changes in female rats exposed to intrauterine hyperglycemia and postweaning consumption of high-fat diet - Paula, Veronyca Goncalves [UNESP]; Sinzato, Yuri Karen [UNESP]; Moraes-Souza, Rafaianne Queiroz de [UNESP]; Soares, Thaigra Sousa [UNESP]; Gallego Souza, Franciane Quintanilha [UNESP]; Karki, Barshana [UNESP]; Andrade Paes, Antonio Marcus de; Corrente, Jose Eduardo [UNESP]; Damasceno, Débora Cristina [UNESP]; Volpato, Gustavo Tadeu (Oxford Univ Press Inc, 2021)
We evaluated the influence of the hyperglycemic intrauterine environment and postweaning consumption of a high-fat diet (HFD) on the glycemia, insulin, lipid, and immunological profile of rat offspring in adulthood. Female rats received citrate buffer (Control-C) or Streptozotocin (a beta cell-cytotoxic drug to induce diabetes-D) on postnatal day 5. In adulthood, these rats were mated to obtain female offspring, who were fed a standard diet (SD) or HFD from weaning to adulthood (n = 10 rats/group). OC/SD and OC/HFD represent female offspring of control mothers and received SD or HFD, respectively; OD/SD and OD/HFD represent female offspring of diabetic mothers and received SD or HFD, respectively. At adulthood, the oral glucose tolerance test (OGTT) was performed and, next, the rats were anesthetized and euthanized. Pancreas was collected and analyzed, and adipose tissue was weighted. Blood samples were collected to determine biochemical and immunological profiles. The food intake was lower in HFD-fed rats and visceral fat weight was increased in the OD/HFD group. OC/HFD, OD/SD, and OD/HFD groups presented glucose intolerance and lower insulin secretion during OGTT. An impaired pancreatic beta-cell function was shown in the adult offspring of diabetic rats, regardless of diet. Interleukin (IL)-6 and IL-10 concentrations were lower in the OD/HFD group and associated to a low-grade inflammatory condition. The fetal programming was responsible for impaired beta cell function in experimental animals. The association of maternal diabetes and postweaning HFD are responsible for greater glucose intolerance, impaired insulin secretion and immunological change. Summary sentence Summary Sentence The association of maternal diabetes and postweaning HFD causes glucose intolerance due to beta-cell disarrangement and impaired insulin secretion, and immunological changes in adult offspring.
Keywords: fetal programming; high-fat diet; diabetes; rat